Endophytic Fungi Around Campus Building : Notes and Biocontrol Potency - Ivan Permana Putra (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Endophytic fungi occupied healthy plant tissues without destroying or producing substances which lead an infection to the host cell.Studies on endophytic fungi and its utilization have gained significance during therecent years in Indonesia. However, information provide in the term of institutional area are limited, and campus building is no exception. the goal of this study was to isolate endophytic fungi from some Angiosperms around IPB University Campus Building (IPBUCB) and testing their potential utilization as biocontrol of some plant pathogenic fungi. A total of 9 isolates of endophytic fungi obtained from this study. All isolates shown unique characteristics on PDA medium. Most of isolates have inhibition activity againtsplant pathogenic fungi. ARIV1 and ARIV2 were performed the highest (%) of inhibition of Phythopthoracapsiciwhile BWIV1 in Fusarium oxisporumf. sp. cubense. This research is an early step to reveal the potential of endophytic fungi around campus building in the foreseeable future.